ANALYSIS OF THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON RISK, PERFORMANCE, AND COMPANY VALUE (GOOD MANAGEMENT THEORY BASED TESTING) - Sandy Mauk, Sarlince (Jurnal Manajemen Bisnis Dan Organisasi, 2022)
The polemic of the company's existence in the community can provide both positive and negative aspects. The company certainly provides goods and services that are needed by the community, but on the other hand, it is not uncommon for people to get bad impacts from the company's business activities. Environmental pollution, products that endanger health, exploitation of labor and irresponsible use of energy are examples of negative forms caused by companies. Many companies are seen as contributing to economic and technological progress, but are criticized for creating social and environmental problems. Then how to make the implementation of this Corporate Social Responsibility program run well? First, the company must empower the community in market development programs and image formation to the community (Community Development Program). According to good management theory and Slack Resource Theory, the company will first focus on the company's performance according to the slack resource theory, and the company will prioritize its focus on social performance (CSR) according to the principles of good management theory. Empirical evidence obtained that a high firm value does not guarantee the existence of corporate responsibility. On the other hand, companies that implement Corporate Social Responsibility will affect the value of the company.